Guía didáctica para la lectoescritura en estudiantes de décimo año de educación general básica. Una propuesta para los docentes de la Unidad Educativa Fiscomisional San patricio – Quito. - Andrade Guaita, Alisson Estefanía (2023)
The following methodological guide aims to motivate reading and writing in Tenth grade EGB. The guide shows content about what gamification is, reading and writing, and develops playful activities. The origin of the problem was evidenced through interviews and observations during pre-professional practices at the San Patricio Fiscomisional Educational Unit located south of Quito, from 2018 to 2022. Students who have fallen behind in school show difficulties in reading and writing skills, fail to connect or coherently express their ideas orally or in writing, this added to the lack of motivation, aspirations and economic stability causes school dropout. For this, the creation of gamified activities is proposed, which considers that learning occurs from the game together with its own dynamic and mechanical abilities. The proposal contains 5 games; one of them focuses on the development of the life plan; and the other 4 to strengthening skills such as: reading comprehension, sentence construction, visual perception, linguistic development, coherent sentence construction, imaginative development, planning, text writing, written oral expression, self-regulation, coherence and cohesion. Each activity is organized around a theme, objective, skill, activity description, an assessment that will be graded through points earned in the game, and a schedule. This proposal has been socialized with teachers and students, having a high approval rate and we hope that it contributes in educational spaces, reflecting on the use of the ''serius game'' for the development of the whole class and not only as an initial dynamic, because it improves the classroom climate and creates spaces for meaningful and holistic acquisition of learning.